Lateral ideals of ternary semigroups - Iampan, A. (Український математичний вісник, 2007)
In this paper, we give some auxiliary results are also necessary for our considerations and characterize the relationship between the (0-)minimal and maximal lateral ideals and the lateral simple and lateral 0-simple ternary semigroups analogous to the characterizations of minimal and maximal left ideals in ordered semigroups considered by Cao and Xu [5].